PERI-URBAN AREA IDENTIFICATION WITHIN THE KAWASAN PERKOTAAN YOGYAKARTA - Hidayat, Fathiyah Rahmi; Keliwar, Khairi Ahza Hail; Muhammad, Ummu Kultsum; Pramita, Juwita (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
The expansion of urban functions fosters the creation of new activity centers beyond existing built-up areas, thereby transforming rural landscapes into semi-urban zones. Driven by rapid globalization, technological advancements, and population growth within urban areas, peri-urbanization—as a manifestation of urban expansion—has become an inevitable phenomenon. This phenomenon is evident in the Kawasan Perkotaan Yogyakarta (KPY), which administratively encompasses three jurisdictions: Yogyakarta City as the urban core, along with portions of Sleman and Bantul Regencies. Currently, the trajectory of urban sprawl is shifting southward toward Bantul Regency. This study aims to delineate the peri-urban zones within the Kawasan Perkotaan Yogyakarta (KPY). This research employs a quantitative approach utilizing Geographic Information System (GIS)-based spatial analysis. Regional clustering was performed using the k-means algorithm based on four primary variables: percentage of built-up land, net population density, percentage of non-agricultural households, and availability of public facilities. The results indicate that peri-urban areas in the KPY are no longer confined by administrative boundaries but have significantly expanded southward into Bantul Regency. The study classifies the region into four distinct zones: (1) urban core, (2) urban fringe, (3) peri-urban, and (4) rural. These findings indicate a substantial transformation of agricultural land into non-agricultural use within the peri-urban zone. Consequently, this study recommends the integration of cross-regional spatial planning policies within the KPY to control land conversion and ensure sustainable development in these transitional areas.